Prevalence of autoimmune thyroid disease in patients with psoriasis: a meta-analysis - Peng Zhang; Ruifang Wu; Xiaochao Zhang; Suhan Zhang; Siying Li; Yuwen Su (BMJ Open)
Objective Psoriasis is a chronic inflammatory disease with autoimmune aetiology. A possible link between psoriasis and autoimmune thyroid disease (AITD) has been suggested in some studies with inconsistent findings. This meta-analysis aims to determine the association between psoriasis and AITD.Design A meta-analysis of observational studies.Data sources PubMed, EMBASE, Scopus and the Cochrane Library were searched up to 1 November 2021.Eligibility criteria for selecting studies We included non-randomised studies, each with over 50 cases in every group, focusing on the rate of comorbidity between psoriasis and AITD.Data extraction and synthesis Two independent reviewers screened the articles and extracted data. The restricted maximum-likelihood was applied to perform the meta-analysis. OR and 95% CIs were pooled to compare the prevalence of AITD in psoriasis and control groups. Heterogeneity was assessed with I2 statistic. The Newcastle-Ottawa Scale and Agency for Healthcare Research and Quality were applied for quality assessment. The risk of bias was assessed with Risk Of Bias In Non-randomised Studies-of Interventions (ROBINS-I).Results Eleven available studies with data on 253 313 patients with psoriasis and 1 376 533 controls were included. Meta-analysis showed that patients with psoriasis had a higher prevalence of AITD (OR 1.76, 95% CI 1.35 to 2.28, Z=4.25, p<0.01), especially loss-of-function disorder of the thyroid gland. Both thyroglobulin antibodies positive rate (OR 1.98, 95% CI 1.27 to 3.10, Z=3.00, p<0.01) and thyroid peroxidase antibodies positive rate (OR 2.15, 95% CI 1.31 to 3.52, Z=3.05, p<0.01) were also increased in the psoriasis group compared with the control group.Conclusions Our study indicates that the rate of co-occurring AITD was significantly increased in patients with psoriasis. It suggests that the increased risk of AITD should be concerned in patients with psoriasis.PROSPERO registration number CRD42020206005.